Ethanol extracts of Rhaponticum uniflorum (L.) DC flowers attenuate doxorubicin-induced cardiotoxicity via alleviating apoptosis and regulating mitochondrial dynamics in H9c2 cells. (24th April 2022) - Hu, Boqin; Zhen, Dong; Bai, Meirong; Xuan, Tianqi; Wang, Yu; Liu, Mingjie; Yu, Lijun; Bai, Dongsong; Fu, Danni; Wei, Chengxi
Abstract: Ethnopharmacological relevance: Loulu flowers (LLF) is the inflorescence of Rhaponticum uniflorum (L.) DC. (R. uniflorum), a member of the Compositae family. This plant possesses heat-clearing properties, detoxification effects, and is therefore frequently used for the treatment of cardiovascular diseases. Aim of this study : This study aimed to investigate the cardioprotective effects of ethanol extracts of LLF against doxorubicin (DOX)-induced cardiotoxicity and explore the associated mechanisms. Material and methods: Ethanol extracts of LLF were prepared and analyzed by LC-ESI-MS/MS. DOX-treated H9c2 cells and DOX-treated zebrafish models were used to explore the cardioprotective effect of ethanol extracts on myocardial function. The effects of LLF on DOX-induced cytotoxicity in H9c2 cells were investigated by MTT assay. Reactive Oxygen Species (ROS) levels, mitochondrial membrane potential (MMP), and nuclear translocation of NF-κB p65 were examined using fluorescent probes. The expression level of Bax, Bcl-2, PARP, caspase-3, cleaved-caspase3, caspase9, IκBα, p-IκBα, IKK, p-IKK, p65, p-p65, OPA1, Mfn1, MFF and Fis 1 and GAPDH was determined by western blotting. Results: Twenty-five compounds were detected in ethanol extracts of LLF, include Nicotinamide, Coumarin, Parthenolide, and Ligustilide. Pre-treatment with LLF attenuated the DOX-induced decrease in viability and ROS production in H9c2 cells. Moreover, LLF treatment maintained the mitochondrial membrane integrity and suppressed apoptosis by upregulating expression level of Bcl-2 and downregulating the expression level of Bax, cleaved-caspase-3, cleaved-caspase-9 and cleaved-PARP. In addition, LLF significantly inhibited the DOX-induced activation of NF-κB signaling. Cells treated with DOX showed aberrant expression of mitochondrial dynamics related proteins, and these effects were alleviated by LLF pre-treatment. In conclusion, these results show that LLF can alleviate DOX-induced cardiotoxicity by blocking NF-κB signaling and re-balancing mitochondrial dynamics. Conclusion: Ethanol extracts of LLF is a potential treatment option to against DOX-induced cardiotoxicity. Graphical abstract: Image 1 Highlights: Twenty-five compounds were detected in the ethanol extracts of LLF, Nicotinamide, Coumarin, Parthenolide etc. The ethanol extracts of LLF can alleviates DOX-induced cardiotoxicity by inhibiting cardiomyocyte apoptosis.